Teacher’s Professional Competence - Rahmawati, Anisa Fitria; Pupun Nuryani (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This paper aims to describe the professional competence of teachers. There are issues or assumptions that develop that the problems are done by teachers such as, some teachers lack sufficient competence, especially professional competency. because the teacher plays a major role in the development of education and largely determines the success of students, especially in the teaching and learning process. The teacher is a component that is very influential on the creation of quality educational processes and outcomes. The research method used is literature review. Competence is a specific standard regarding the performance or skills of a person that is applied at a job or in society. The results of this paper can be used as a basis for a person's performance to work well, measurable, specific or standardized and for research in the development of other educational sciences, Teachers who have professional competence must be able to sort and select and classify learning material that will be delivered to students